2020
DOI: 10.1186/s13059-020-02132-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic evaluation of single-cell RNA-sequencing imputation methods

Abstract: Background: The rapid development of single-cell RNA-sequencing (scRNA-seq) technologies has led to the emergence of many methods for removing systematic technical noises, including imputation methods, which aim to address the increased sparsity observed in single-cell data. Although many imputation methods have been developed, there is no consensus on how methods compare to each other. Results: Here, we perform a systematic evaluation of 18 scRNA-seq imputation methods to assess their accuracy and usability. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
204
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(210 citation statements)
references
References 96 publications
6
204
0
Order By: Relevance
“…This is likely due to the fact that a small cluster of NP cells were mixed with H1 cells after imputation by MAGIC ( Fig 3 ), resulting in compromised performance in marker gene identification. Our results were largely consistent with a previous evaluation of imputation methods in identifying differentially expressed genes using Fluidigm C1 data [ 33 ]. No genes achieved significance in the imputed data by SAUCIE, so the result of SAUCIE could not be shown.…”
Section: Resultssupporting
confidence: 90%
“…This is likely due to the fact that a small cluster of NP cells were mixed with H1 cells after imputation by MAGIC ( Fig 3 ), resulting in compromised performance in marker gene identification. Our results were largely consistent with a previous evaluation of imputation methods in identifying differentially expressed genes using Fluidigm C1 data [ 33 ]. No genes achieved significance in the imputed data by SAUCIE, so the result of SAUCIE could not be shown.…”
Section: Resultssupporting
confidence: 90%
“…To evaluate ability of these tools on meaningfully extracting transcriptional heterogeneity, we assessed that the cell-type-specific obtained from PAS should be retained in dimensional reductional space and could assign cells into cell populations through unsupervised clustering or supervised classification [20] , [24] , [26] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] . Therefore, the accuracy of PAS transformation methods were assessed by three methods of dimensional reduction, clustering and cell type annotation.…”
Section: Methodsmentioning
confidence: 99%
“…In the past years, many single-cell specific imputation tools have already been published [15, 11, 27] and their evaluation showed that denoising sparse simulated data can, for example, help to reobtain original cell clusters and time-course patterns [10]. Because of the rapid increase of published imputation methods, several review articles [20, 7] and benchmarking analysis [40, 25] have been published in recent months, also investigating specific fields within the downstream analysis realm, such as differential gene expression [14]. Unsupervised clustering of cells represents another common downstream tool in the analysis of scRNA-seq data which allows for later cell type classification.…”
Section: Introductionmentioning
confidence: 99%